2000
DOI: 10.1038/35010020
|View full text |Cite
|
Sign up to set email alerts
|

Roles of E. coli DNA polymerases IV and V in lesion-targeted and untargeted SOS mutagenesis

Abstract: The expression of the Escherichia coli DNA polymerases pol V (UmuD'2C complex) and pol IV (DinB) increases in response to DNA damage. The induction of pol V is accompanied by a substantial increase in mutations targeted at DNA template lesions in a process called SOS-induced error-prone repair. Here we show that the common DNA template lesions, TT (6-4) photoproducts, TT cis-syn photodimers and abasic sites, are efficiently bypassed within 30 seconds by pol V in the presence of activated RecA protein (RecA*), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
463
2
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 422 publications
(504 citation statements)
references
References 28 publications
36
463
2
3
Order By: Relevance
“…While non-enzymatic ligation methods may offer some advantages, one limitation of the photoligation strategy relative to enzymatic methods is the fact that the CPD analogue as the ligated structures differs from that of the natural DNA junction, which is likely to interfere with further manipulation (such as amplification). However, in vitro analyses have shown that some DNA polymerases can copy distorted DNA templates containing a UV-induced lesion [16][17][18]. Additionally, because a single bond is included in the structure, d(T-CV U) has higher flexibility than usual CPD (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…While non-enzymatic ligation methods may offer some advantages, one limitation of the photoligation strategy relative to enzymatic methods is the fact that the CPD analogue as the ligated structures differs from that of the natural DNA junction, which is likely to interfere with further manipulation (such as amplification). However, in vitro analyses have shown that some DNA polymerases can copy distorted DNA templates containing a UV-induced lesion [16][17][18]. Additionally, because a single bond is included in the structure, d(T-CV U) has higher flexibility than usual CPD (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Although Reuven et al, who have successfully reconstituted UmuDЈ 2 Cdependent lesion bypass in vitro, found it to be completely independent of the ␤ clamp of Pol III (43), Tang et al, using a slightly different approach to reconstitute UmuDЈ 2 C-dependent TLS in vitro (63), reported a strict requirement of both the ␤ clamp and the five-subunit clamp loader (␥ complex) of Pol III for lesion bypass. This difference with respect to the requirement of the ␤ clamp for TLS in vitro has been attributed to differences in the template DNAs and the levels of RecA protein used by these two groups (62,67), although it could also be due to the maltose binding protein-UmuC fusion protein utilized by Reuven et al (67).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that interactions of ␤ with the umuDC gene products are important for both the DNA damage checkpoint control (57) and TLS (62,63) and that self-cleavage of UmuD to yield UmuDЈ serves to modulate the interactions of UmuD 2 C and UmuDЈ 2 C with ␤ to effect the release of the checkpoint control and enable TLS (57). In any event, a definitive answer regarding the role of the ␤ clamp in TLS in the living cell will likely require a combined biochemical and genetic approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations